EFFECTS OF ANXIETY ON IN-CLASS SPEAKING PERFORMANCE AMONG ULIS FIRST-YEAR MAINSTREAM ENGLISH MAJORS - Nguyễn, Phương Thảo (2021)
Firstly, the paper is expected to find out the factors contributing to anxiety among first- year mainstream EFL students in foreign language classes at ULIS. Secondly, a closer look will be taken at anxiety manifestation in students when they speak in foreign language classes. Finally, the effects of anxiety on students‘ in- class speaking performance as perceived by the students will be focused so that both students and teachers have suitable ways to soothe those effects